STUDIES OF BIOCHEMICAL AND HAEMATOLOGICAL CHANGES IN LOCAL BREED CATTLE NATURALLY- INFECTED WITH FASCTOLA GIGANTICA - A.Makkawi, Talib; 0.Youhana, S. (The Iraqi Journal of Veterinary Medicine, 1989)
This study was conducted by evaluate some haematological and biochemical changes caused by F. gigantica. The haematological and biochemical changes were studied, by taking samples of blood collected from jugular veins of animals slaughtered in the abattoir. The disease in its two phases (acute and chronic) did not cause any significant change in total serum protein. The increased amount of serum GOT in both phases could be considered as an indicator of the liver damage. However, the total serum bilirubin is not a good indicator of liver function except in some severe chronic cases.